THE RESPON PENINGKATAN TEKANAN DARAH TERHADAP PEMBERIAN PELATIHAN PASSIVE RANGE OF MOTION TIGA PULUH MENIT PADA LANSIA DI PANTI SOSIAL TRESNA WERDA WANA SERAYA DENPASAR - Adhitya, I Putu Gde Surya; Wibawa, Ari; Indrayani, Agung Wiwiek (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Passive Range Of Motion (PROM) is given to elderly to prevent complications that occur in the long immobilization conditions. The aimed of this study is there any improvement response of blood pressure after giving PROM for thirty minutes and how much is the improvement. This research is an experimental study with the method of one-group pretest-posttest design, with 10 peoples sample, the elderly (> 60 years), without having a chronic illness. Elderly who difable don’t be included in this study. The sampling technique used is the saturated sampling. This study was conducted over three days, each day was measured before treatment and after treatment to see the response of blood pressure increase caused by PROM thirty minutes of training in the elderly. Data were analyzed using SPSS computer software that is shapiro wilk test to test of normality distribution and paired t-test or the wilcoxon signed rank test. The result of wilcoxon sign rank test on the first day, systolic p = 0.005 (p <0.05) and diastolic p = 0.005 (p <0.05) seen here there is a significant difference. The results of paired t-test test to see the difference in the response of blood pressure in systole and diastole second day and third day, on the second day systolic p = 0.005 (p <0.05); diastole p = 0.012 (p <0.05); on the third day systole p = 0.0001 (p <0.05); and on the third day of diastole p = 0.015 (p <0.05), it seemed that there were significant differences in systolic and diastolic blood pressure in the second and third days. The conclusion of this study is the response of blood pressure after PROM exercise is 5 – 8 mm Hg for systolic, and 3 – 4 mm Hg for diastolic.
Keywords: Elderly, Training Passive Range Of Motion, Blood Pressure.